1993
DOI: 10.1080/01688639308402561
|View full text |Cite
|
Sign up to set email alerts
|

Forgetting rates for verbal, pictorial, and figural stimuli

Abstract: Literature on forgetting rates is reviewed and related methodological issues are discussed. Descriptive data from 50 subjects are provided for tests which were developed to assess forgetting rates for words, pictures and designs. The three tests are well-matched on initial learning at criterion and have comparable variance and skewness of score distributions. Forgetting rates were similar across the initial 10-min retention interval, but there was a more rapid loss of words than pictures and designs from 10 mi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
14
0

Year Published

1995
1995
2015
2015

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(14 citation statements)
references
References 41 publications
0
14
0
Order By: Relevance
“…In principle, this allows assessment of whether particular forms of information are forgotten at different rates in people with epilepsy, and improves the generalizability of findings (Hart & O'Shanick, 1993). Assessing forgetting rates for different types of material also helps assess whether rapid forgetting reflects a general memory consolidation/stabilisation deficiency or deficits in information processing or memory for particular types of information.…”
Section: Part I: Methodological Issues In Assessing Forgetting Ratesmentioning
confidence: 99%
“…In principle, this allows assessment of whether particular forms of information are forgotten at different rates in people with epilepsy, and improves the generalizability of findings (Hart & O'Shanick, 1993). Assessing forgetting rates for different types of material also helps assess whether rapid forgetting reflects a general memory consolidation/stabilisation deficiency or deficits in information processing or memory for particular types of information.…”
Section: Part I: Methodological Issues In Assessing Forgetting Ratesmentioning
confidence: 99%
“…For example, Hart et al (1987) used a much briefer (and easier) test to match their participants at 90 s than they used to measure forgetting at subsequent delays, that is, they were not comparing like with like (Kopelman, 1992a(Kopelman, , 1992b. More recently, Hart and O'Shanick (1993) have examined recognition memory for pictures, designs, and words in head injury patients at 90 s and beyond, claiming faster forgetting in picture recognition. However, this emerged in only one form of analysis, and it is noticeable that the results of repeated measures analysis of variance (ANOVA) were not reported.…”
mentioning
confidence: 99%
“…198)." More recently, studies by Kargopoulos, Bablekou, Gonida, and Kiosseoglou [2003] as well as, the study by Hart and O'Shanick [1993], found that pictures are more effective than other types of formats in improving memory retention. Mayer [Richard E. Mayer, 2001] reported that visual representations generally enhance the recall of information over a series of studies but with some caveats that competing channels of information can negatively impact learning.…”
Section: Power Of Visual Literacymentioning
confidence: 99%